2019
DOI: 10.1177/0886260519843284
|View full text |Cite
|
Sign up to set email alerts
|

Weighing Risk Factors for Adolescent Victimization in the Context of Romantic Relationship Initiation

Abstract: Research has paid little attention to the link between the characteristics of the relational context where adolescents are likely to initiate their romantic relationships and teen dating violence (TDV). Hence, the findings are still scattered. This study examined different risks in the female teenagers' relational context (peer group characteristics, participants' risky activities, and pressure to start dating) and their TDV victimization, which had not been previously studied in the Spanish population. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…This event can negatively affect girls’ psychosocial wellbeing, for instance, when the peer group pressures them to start a relationship [ 15 ], related to later relational victimization [ 16 ]. Previous research has found evidence of peer group pressure on girls to start a relationship [ 17 ] and of the mirage of upward mobility in the Spanish context. It consists of girls’ mistaken perception of having an intimate relationship with boys responding to dominant traditional masculinity and raising their attractiveness and status.…”
Section: Introductionmentioning
confidence: 99%
“…This event can negatively affect girls’ psychosocial wellbeing, for instance, when the peer group pressures them to start a relationship [ 15 ], related to later relational victimization [ 16 ]. Previous research has found evidence of peer group pressure on girls to start a relationship [ 17 ] and of the mirage of upward mobility in the Spanish context. It consists of girls’ mistaken perception of having an intimate relationship with boys responding to dominant traditional masculinity and raising their attractiveness and status.…”
Section: Introductionmentioning
confidence: 99%
“…Database and Google Scholar searches identified 7,347 unique records (Figure 1), of which 477 were retained to screen on full text and 21 were eligible for inclusion (Aizpitarte et al, 2017; Antônio et al, 2012; Enosh, 2007; Flisher et al, 2007; Foshee et al, 2001; Gagné et al, 2005; Gonzalez-Mendez et al, 2019; Hébert et al, 2019; Helland, 1998; Hopper, 2011; Kernsmith & Tolman, 2011; Kinsfogel & Grych, 2004; Peskin et al, 2017; Pöllänen et al, 2021; Price, 2002; Reed et al, 2011; Reyes et al, 2016; Shamu et al, 2016; Shorey et al, 2018; Van Ouytsel et al, 2020; Wesche & Dickson-Gomez, 2019), reporting on 21 unique studies. Two reports presented analyses of different social norms measures from the same randomized controlled trial (Foshee et al, 2001; Reyes et al, 2016) and were therefore treated as two unique studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, 11 were conducted in the United States (Foshee et al, 2001; Helland, 1998; Hopper, 2011; Hunt et al, 2022; Kernsmith & Tolman, 2011; Kinsfogel & Grych, 2004; Peskin et al, 2017; Reed et al, 2011; Reyes et al, 2016; Shorey et al, 2018; Wesche & Dickson-Gomez, 2019), three in Canada (Gagné et al, 2005; Hébert et al, 2019; Price, 2002), three in South Africa (Flisher et al, 2007; Pöllänen et al, 2021; Shamu et al, 2016), three in Spain (Aizpitarte et al, 2017; Gonzalez-Mendez et al, 2019; Nardi-Rodríguez et al, 2022), one in Belgium (Van Ouytsel et al, 2020), one in Brazil (Antônio et al, 2012), one in Israel (Enosh, 2007), and one in Niger (Shakya et al, 2022). All studies were observational, and seven (Enosh, 2007; Foshee et al, 2001; Peskin et al, 2017; Pöllänen et al, 2021; Reyes et al, 2016; Shakya et al, 2022; Shamu et al, 2016) analyzed data collected as part of an evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations